Growth and Production of Mustards on Various Compositions Growing Media and Types of Fertilization - R. Rahmawati (Universitas Sembilanbelas November Kolaka, 2021)
This study aimed to determine the effect of composition of growing media and types of fertilization on the growth and production of mustard plants. This study was carried out at the Experimental Garden of Uniprima-Sengkang from February to April 2020, using a randomized block design with two treatment factors, namely the growing media consisting of soil (control), manure + soil (1: 1), bokashi + soil ( 1: 1), and soil + manure + Bokashi (1:1:1) and fertilization, namely: without urea and Azotobacter, urea 50 kg ha1 (0.2 g/plant), Azotobacter, urea 50 kg ha-1 (0.1 g/plant+ Azotobacter). The results showed that the composition of the growing medium Soil + Manure + Bokashi (1:1:1) and fertilization with ½ Urea 50 kg ha-1 (0.1 g/plant) + Azotobacter tended to show higher result in the parameters of plant height, number of leaves, leaf width and plant weight than other treatments, however, it statistically showed no interaction between the composition of the growing media and fertilization